Methodological issues in digital conversation analysis. (August 2021) - Jucker, Andreas H.
Abstract: In this discussion paper, I review some of the critical issues that arise when the methodological tools of Conversation Analysis are applied to digital discourse. Conversation Analysis is an approach that has been developed for the investigation of everyday, spoken interactions, typically in face-to-face situations or on the telephone. The transfer of its methods to written digital discourse via instant messaging applications begs a number of important questions. A brief overview of the papers assembled in this collection of articles reveals that it is the persistence and the asynchronous or quasi-synchronous nature of digital discourse that stand out as the central features requiring an adaptation of the methodological tools. These lead to significant differences in the sequentiality of conversational contributions and in the way turn-taking is adapted to the new environment. I also highlight the repurposing – or recontextualization – of existing resources for new functions in new contexts as a further common thread that unites the contributions of this collection of articles.